Answer:
(- 6, 0 )
Step-by-step explanation:
Given the 2 equations
3x + 2y = - 18 → (1)
2x + 9y = - 12 → (2)
Multiplying (1) by 2 and (2) by - 3 and adding will eliminate the term in x, that is
6x + 4y = - 36 → (3)
- 6x - 27y = 36 → (4)
Add (3) and (4) term by term to eliminate x
- 23y = 0
y = 0
Substitute y = 0 into either of the 2 equations and evaluate for x
Substituting into (1)
3x + 0 = - 18
3x = - 18 ( divide both sides by 3 )
x = - 6
Solution is (- 6, 0 )
Range is output for given input
domain is D={-3,0,5}
input -3,0 and 5 for x
f(-3)=(-3)^2-6(-3)+4
f(-3)=9+18+4
f(-3)=31
F(0)=(0)^2-6(0)+4
f(0)=0-0+4
f(0)=4
f(5)=(5)^2-6(5)+4
f(5)=25-30+4
f(5)=-1
Domain={-3,0,5}
Range={31,4,-1}
Answer:
3x + y = 21
x = 2.5
7.5 + y = 21
y = 13.5
shirt cost $13.50
Step-by-step explanation:
Answer:
x>14
Step-by-step explanation:
Step 1: Simplify both sides of the inequality.
−4>−2x+24
Step 2: Flip the equation.
−2x+24<−4
Step 3: Subtract 24 from both sides.
−2x+24−24<−4−24
−2x<−28
Step 4: Divide both sides by -2.
−2x−2<−28−2
x>14